An autopsy and histopathology-based study to ascertain the cause of death of brought dead cases - Chandan Bandyopadhyay; Prabir Chandra Paul; Prabhas Chandra Chakraborty (Wolters Kluwer Medknow Publications, 2024)
Background and Objectives: The cases of apparent natural deaths are encountered in the hospital casualties who are noted dead at the time of the first medical attention and as such are labeled as "Brought Dead." These include the cases of sudden death, unexplained death, and unattended death. The cause of such deaths is reported in the literature to emanate principally from the cardiovascular system, though there are some documented geographical, racial, and other variations. In the present study, we endeavored to detect the cause of such natural deaths in terms of the disease and the organ system involved, in the deceased individuals of the contemporary Bengali population, with cases due to obvious unnatural causes being excluded. Materials and Methods: An observational, cross-sectional study with 105 (n = 105, male: 89, female: 16) study subjects of age group of 20-80 years, selected by systemic random sampling, from the brought dead subjects coming to the mortuary of the NRS Medical College and Hospital for medicolegal autopsy from April 2011 to March 2012, excluding cases having a history of the obvious unnatural event. Organ system-wise gross examination was done, followed by tissue sampling for histopathological examination. The case-wise findings were tabulated and analyzed for descriptive statistics using SPSS software. Results: In the present study, 89 cases were male (84.8%) and 16 cases were female (15.2%), which reflects a male: female ratio of 5.56:1. The dead bodies are mostly recovered from the footpaths (47 cases, 44%). Sixty-four (61%) cases are of known identity. In 54 cases out of 105 (51.4%), morbid pathology is detected in the respiratory system (RS), lobar pneumonia, and cavitary pulmonary tuberculosis being the most frequent disease entity, in both genders. Fifty-one years-sixty-five years is found to be the most commonly affected age group, in both genders. Interpretation and Conclusions: The present study shows that the most common organ system involved in brought dead cases is the RS, which is supported by a few Indian studies.